Ag nanoparticles/hematite mesocrystals superstructure composite: a facile synthesis and enhanced heterogeneous photo-Fenton activity. Issue 12 (1st February 2016) - Chen, Xianjie; Chen, Fangge; Liu, Fenglin; Yan, Xiaodong; Hu, Wei; Zhang, Ganbing; Tian, Lihong; Xia, Qinghua; Chen, Xiaobo
Abstract : The synergistic effect of the unique superstructure and the Ag loading resulted in the effective separation of charge carriers and excellent photo-Fenton performance of Ag/hematite mesocrystals. Abstract : Mesocrystals, as a new class of crystals, compared to the more common single crystals and polycrystalline systems, have attracted unparalleled attention owing to their unique ordered superstructure. Herein, uniform, highly crystalline, nanoporous and cocoon-like hematite mesocrystals have been fabricated through a facile template-free approach in benzyl alcohol. They showed a relatively large surface area of 18.8 m 2 g −1 and an average pore size of 3.67 nm, which was within the range of hole diffusion lengths (2–4 nm) of α-Fe2 O3 . The loading of Ag nanoparticles on the α-Fe2 O3 mesocrystals had no distinct effect on the surface area and pore distribution. The results of photoluminescence and photoelectrochemical measurements indicated that the synergistic effect of the suitable pore size and Ag nanoparticles resulted in effective charge carrier transfer. Thus, the Ag/hematite mesocrystal composites displayed high photo-Fenton activity in the oxidation of Rhodamine B, methyl orange and glyphosate under visible light.